Challenges and Barriers Experienced by Medical colleges faculty members in Conducting Research, University of Benghazi - Lamya El Adouli,; Hadir Gawili,; Souad El-mani,; Naeima Houssein,; Mailud El-amari, (AlQalam Journal of Medical and Applied Sciences, 2025)
Scientific research is a methodical investigation designed to address a problem and serves as a primary catalyst for societal advancement, regarded as a crucial indicator of growth. In addition, the university's scientific research plays a significant role in improving the community. Accordingly, the present study attempts to investigate challenges faced in conducting research from the perspective of Medical Faculty members at Benghazi University. A descriptive cross-sectional study was conducted to accomplishment of research question. The questionnaire selected as a tool, the online questionnaire, has been distributed in a Google Form for ease and efficient data collection. The questionnaire was adopted from previous literature and validated by experts. The quantitative data that gathered from teaching staff from the medical faculty's Public Health, Pharmacy, Biomedical Science, Medicine, and Dentistry, and analyzed by SPSS version 26. The statistical tests used were percentages, frequencies, and means. One of the more significant findings to emerge from this study is that the most reported barrier was personal challenges. The findings indicate that 84 )56.0%) participate in terms of personal challenge. The statement of (The pressures resulting from the faculty member's obligations) was higher than the other statements. Just about 23 (15.3%) of medical faculty members indicated that the lack of foreign languages in which scientific journals are issued is a personal challenge. In addition, based on the results, the second barrier from the point of view of participants was the institutional and administrative. Financial constraints and Social and cultural barriers ranked third and fourth as barriers to the results of this study, respectively. The last barrier was the technical and infrastructural limitations. The findings indicate that research activity is hindered by personal limitations, including time constraints and skill deficiencies, as well as by broader institutional, financial, technical, and societal factors. Future research should investigate these barriers in depth by using a qualitative study approach.